Drought stress effect, tolerance, and management in wheat – a review - Shivalal Nyaupane; Mukti Ram Poudel; Binod Panthi; Anjali Dhakal; Harikala Paudel; Radhakrishna Bhandari (Cogent Food & Agriculture)
Wheat is the most important cereal crop in the world. It contributes as a major source of protein and calories in the daily human diet. Drought has become a major abiotic stress that severely affects wheat production globally. Changing rainfall patterns, increased atmospheric CO2 levels, rises in atmospheric temperature and hot and dry winds are the major causes of drought stress. It has morphological, physiological, and biochemical consequences such as reduced yield performance, yield attributing parameters, germination, and seed vigor, early leaf senescence, early maturity, decreased chlorophyll content, decreased Rubisco activity, decreased photosynthesis, and decreased starch accumulation. Drought produces reactive oxygen species that cause oxidative damage to the plants leading to programmed cell death. Wheat plant has developed various tolerance mechanisms such as drought escape, avoidance, and tolerance to protect them from drought. Increasing trichome density and leaf waxiness, root: shoot ratio, stay green, accumulation of proline, production of various enzymes viz; superoxide dismutase (SOD), ascorbate (APX), peroxidase (POD), catalase (CAT), osmotic adjustment, ABA accumulation, and formation of dehydrins leads to drought tolerance. Screening of the various genotypes for the identification of novel trait combinations, genetic engineering, and transgenic approaches (incorporates, transfer, and introduces the desirable gene into the desired plants) and thereby the adaptable varieties can be selected and induced to develop new varieties with desired characteristics would be a major genetic management strategies to overcome drought, increase production, and ensure the food and nutritional security of the world.